Implementation of Multicultural Islamic Education Values in Schools in Indonesia: Systematic Literature Review - Wahfiuddin Al Musyarrofi; Mohammad Rofiq (FKIP, Universitas Palangka Raya, 2025)
Multiculturalism presents a significant challenge to contemporary social development, particularly in Indonesia, a nation characterized by its vast ethnic, religious, and cultural diversity. Multicultural Islamic education is viewed as a strategic solution to fostering social harmony and mitigating potential conflicts based on ethnicity, religion, race, and intergroup relations (SARA). This study employs a qualitative approach using the Systematic Literature Review (SLR) method based on the PRISMA framework to analyze various references related to the implementation of multicultural Islamic education values in schools. The findings indicate that Islamic Religious Education (PAI) plays a crucial role in instilling values of tolerance, respect for diversity, and democratic attitudes among students. However, the implementation faces several challenges, including a lack of parental support, limited learning media, and insufficient time allocation for promoting multicultural values. Therefore, effective strategies are needed, such as integrating Islamic concepts into multicultural education, strengthening an inclusivity-based curriculum, and enhancing teachers' capacity to deliver diversity-respecting instruction. The findings highlight the strategic role of Islamic religious education in preventing radicalism and promoting national unity through inclusive multicultural education